2022
DOI: 10.2337/dc21-0507
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Glycemic Control Among Youth and Young Adults With Diabetes: The SEARCH for Diabetes in Youth Study

Abstract: OBJECTIVES To describe temporal trends and correlates of glycemic control in youth and young adults (YYA) with youth-onset diabetes. RESEARCH DESIGN AND METHODS The study included 6,369 participants with type 1 or type 2 diabetes from the SEARCH for Diabetes in Youth study. Participant visit data were categorized into time periods of 2002–2007, 2008–2013, and 2014–2019, diabetes durations of 1–4, 5–9, and ≥10 years, and age g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 45 publications
0
18
0
1
Order By: Relevance
“…The likelihood of acquiring severe diabetic complications in DM is decreased by therapies such as intensive insulin therapy that strictly and consistently limit glucose excursions [7] . Tight control of blood glucose levels is challenging to maintain [8] . Hence research has been done to develop new, powerful anti‐diabetic medications that work through several methods [9] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The likelihood of acquiring severe diabetic complications in DM is decreased by therapies such as intensive insulin therapy that strictly and consistently limit glucose excursions [7] . Tight control of blood glucose levels is challenging to maintain [8] . Hence research has been done to develop new, powerful anti‐diabetic medications that work through several methods [9] .…”
Section: Introductionmentioning
confidence: 99%
“…[7] Tight control of blood glucose levels is challenging to maintain. [8] Hence research has been done to develop new, powerful anti-diabetic medications that work through several methods. [9] Because aldose reductase (EC 1.1.1.21; AR, ALR2) [10] inhibitors (ARIs) do not affect plasma glucose, [11] they pose no danger of hypoglycemia and may be able to stop or slow the course of specific diabetic problems despite high blood sugar levels (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Glycemia has not improved among youth with longstanding T1D despite advancements in diabetes technologies [7]-nearly one-third to one-half have an HbA1c ≥ 9:5% (80 mmol/mol) [5,8]. Glycemia proximal to T1D diagnosis is also critical to manage given that a metabolic memory may persist beyond the period of initial diagnosis to influence future risk of diabetes-related complications [9].…”
Section: Introductionmentioning
confidence: 99%
“…Management of pediatric diabetes is complex, with high rates of youth experiencing elevated blood glucose levels far above recommended glycemic targets; the SEARCH for Diabetes in Youth Study ( Petitti et al, 2009 ) found 17% of youth with T1D and 27% of youth with type 2 diabetes (T2D) had Hemoglobin A1c (HbA1c) levels ≥9.5% and these trends are worsening in youth and young adults ( Malik et al, 2022 ). In addition, since youth with T2D are often treated with insulin therapy and glucose monitoring, they have a similar burden of diabetes management as youth with T1D ( American Diabetes Association Professional Practice Committee et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%